Study guides

☆☆

Q: Solve by substitution 3x plus 2y equals 6 4x-y equals 2?

Write your answer...

Submit

Related questions

2y + 2xy' + 4y + 4xy' = 0 6y + 6xy' = 0 y' = -y/x

4xy+1=3y-7x 4xy-3y=-7x-1 y(4x-3)=-7x-1 y=(-7x-1)/(4x-3)

It is 4xy.

4xy + x3y + yx2 + yx + 3yx = x3y + x2y + 8xy = (xy)(x2y + x + 8)

It is 4xy.

4xy - 2y(x + 4) = 4xy - 2xy - 8y = 2xy - 8y = 2y(x - 4)

(x + 3)(x + 4y)

the difference between 2x2 +4xy-3 and x2-2xy-4 is?

It is 4xy.

If by "What is the answer to", you mean "How do you factor", then we can solve it as follows: x2 + 13xy + 36y2 = x2 + 4xy + 9xy + 36y2 = x(x + 4y) + 9y(x + 4y) = (x + 9y)(x + 4y)

3x2y - 4xy + 4x

-1

4xy

(2x2+4xy-3)-(x2-2xy-4)Answer: x2+6x+1

4x2 - 4xy + y2 = (2x - y)2 so the length of the side of the square must be 2x-y.

Without an equality sign the given expression is not an equation

(3 - y + 2x)(3 + y - 2x)

You need 2 full equations to answer that, or the number for x and what it equals. Without that information that is insolvable.

You cannot add them. The 'y' in the 4xy means that you cannot add it to 3x, since the 'y' is an extra component that the 'x' does not have. You can add 3x to 3x, or 4y to 4y, but you cannot add terms which contain different variables to each other. (It's like trying to add apples and oranges, they're not the same thing).

It stays the same because it does not have any common terms. A: 6y-4xy

4xy/0.25x = 16y

5(x^2 - 4xy + 2y^2)

There is not enough information in the question to determine whether or not the conditional statement is true or false.

4xy + 6xz When factorising algebraic expressions treat them just as ordinary numbers. Ascertain what the common factors are. The factors of 4xy are 2 x 2 x 'x' x y The factors of 6xz are 2 x 3 x 'x' x z The factors common to both expressions are 2 and 'x'. Therefore, 4xy + 6xz = 2x(2y + 3z)

The GCF is 2x.